Analisis Jabatan (Job Analysis, Job Description, Dan Job Specification) Pada Pengembangan Sumber Daya Manusia - Aliya Tsabita; Indah Rahma Zain; Hamdini Putri; Chintya Ones Charli (CV. ITTC INDONESIA, 2026)
Job analysis is a crucial function in human resource (HR) development, aimed at identifying the tasks, responsibilities, and competencies required for a specific job. It encompasses job descriptions and job specifications—elements that are interconnected and support processes such as recruitment, selection, training, career development, and employee performance evaluation. This study employs a literature review method, examining various theories and research regarding job analysis within the context of HR development. The findings indicate that the proper implementation of job analysis can enhance the effectiveness of human resource management and assist organizations in optimally achieving their goals.